IMPROVEMENT OF GAS-BOTTLE IN-FLIGHT PRESSURIZATION - Митиков, Юрий Алексеевич; Артамонов, Александр Игоревич (Eastern-European Journal of Enterprise Technologies, 2012)
Оn account of analysis of thermal conditions of operations gas-bottle fuel tank pressurization system of launch vehicles the possible ways to improve their efficiency– the reduction initial and increase final temperature of the helium balloons are given.